2021
DOI: 10.12911/22998993/140477
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Banana Waste Biochar on Physiological Responses and Growth of Seashore Paspalum

Abstract: The current study aimed to evaluate the effect of banana waste biochar on the physiological traits and growth of Paspalum vaginatum under three water treatments (100%, 80%, and 60% of the water holding capacity (WHC) of the soil). A plastic pot experiment was done for the germination of paspalum vaginatum. The treatments were the addition of compost, banana waste biochar, or banana waste biochar and compost combination to the soil. We used multiple factor analysis (MFA) to reveal the relationship between the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Using the OS5p Modulator Fluorometer (Model OS5p, Opti-Sciences, Hudson, NH, USA), the chlorophyll-fluorescence parameters were measured on three leaves from the same treatment in the afternoon in the dark and in light. Before measuring photosystem-II activity, all leaf samples were kept in the dark for 30 min [11].…”
Section: Experimental Designmentioning
confidence: 99%
“…Using the OS5p Modulator Fluorometer (Model OS5p, Opti-Sciences, Hudson, NH, USA), the chlorophyll-fluorescence parameters were measured on three leaves from the same treatment in the afternoon in the dark and in light. Before measuring photosystem-II activity, all leaf samples were kept in the dark for 30 min [11].…”
Section: Experimental Designmentioning
confidence: 99%
“…In a pot experiment with ten levels of an organic amendment given to a sandy loam poor soil at 20% WHC, this research looked at the effect of peanut hull biochar on P. vaginatum. Based on our previous results, we suggested that peanut hull biochar will improve and ensure physiological traits and paspalum growth even under 20% of WHC considered severe drought conditions [7,8].…”
Section: Introductionmentioning
confidence: 91%
“…For the elemental composition: 0.007% of total nitrogen Nt, 0.201 ‰ of P2O5, 2.5% of total organic matter (Mot), 1.45% of total organic carbon (Cot), 0.357 ‰ of K2O,0.192 ‰ of Na2O,0.933‰ of Cao, and 0.391 ‰ of MgO. The contents of iron, manganese copper and zinc were, respectively, 0.4, 7.4, 0.9, 2.6 ppm [8][9][10][11].…”
Section: Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations